The role of EUS in diagnosis and treatment of liver disorders - Campos, Sara; Poley, Jan-Werner; van Driel, Lydi; Bruno, Marco J. (Endoscopy International Open, 2019)
Background and aim Transabdominal ultrasound (US), computed tomographic scanning (CT) and magnetic resonance imaging (MRI) are established diagnostic tools for liver diseases. Percutaneous transhepatic cholangiography is used to perform hepatic interventional procedures including biopsy, biliary drainage procedures, and radiofrequency ablation. Despite their widespread use, these techniques have limitations. Endoscopic ultrasound (EUS), a tool that has proven useful for evaluating the mediastinum, esophagus, stomach, pancreas, and biliary tract, has an expanding role in the field of hepatology complementing the traditional investigational modalities. This review aimed to assess the current scientific evidence regarding diagnostic and therapeutic applications of EUS for hepatic diseases.